Implementation smart home using internet of things - Afrizal Mayub; Fahmizal Fahmizal; Ma’ruf Shidiq; Unan Yusmaniar Oktiawati; Nur Rohman Rosyid (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Development in technology of information today provides various facilities to support human activity. One technology that facilitates human is the use of automated systems, the application of smart home system makes it easier for users to control household electronic devices. This study addresses one of the smart home solutions with automation systems. The system is built using ESP8266 and Raspberry Pi devices, by utilizing MQTT, REST and Laravel framework protocols. With Arduino, Python and PHP programming, household devices can be controlled both automatically and manually. Control system can be done by using web, chatbot, and physically. The communication used utilizes wireless network. With the designed system, the users can control the device, gain information and get warning. The information provided by the system is obtained from open data on the internet and from the sensor installed on the device.